Regional Trade Arrangements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1992)
Regional trade arrangements have recently attracted growing interest, as existing schemes are either being extended or revived and new groupings are being formed. This study reviews recent initiatives and the experience with regional integration in industrial and developing countries and discusses the implications of the recent expansion of the trend for the multilateral trading system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet